Bismuth scandate-lead titanate based piezoelectric ceramic material as well as preparation method and application thereof

By doping the transition group metal element Me after doping in BiScO3-PbTiO3 ceramics, a new chemical structure is formed, which solves the problem of low piezoelectric anisotropy of PZT ceramic materials, significantly improves the piezoelectric performance and anisotropy, and is suitable for ultrasonicity. Non-destructive testing and water acoustic transducers and other applications.

CN119390440APending Publication Date: 2025-02-07SHANGHAI UNIV

Patent Information

Application Number
CN202411448023.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-17
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

The piezoelectric anisotropy of existing PZT ceramic materials leads to parasitic modal interference in ultrasonic non-destructive detection and hydroacoustic transducer applications, affecting the accuracy and stability of the resonant frequency and reducing resolution.

Method used

(1-y)Bi(Sc(1-x)Mex)O3-yPbTiO3-yPbTiO3 Chemical structure regulates the microstructure and polarization state of ceramics, thereby improving piezoelectric properties.

Benefits of technology

It significantly improves the piezoelectric anisotropy of piezoelectric ceramics, with the maximum piezoelectric constant d33>500pC/N, piezoelectric anisotropy|d33/d31|>3.5, reducing the interference of parasitic mode to the main vibration mode, and enhancing the sound The signal-to-noise ratio and sensitivity of the nanodetection system.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119390440A_ABST
    Figure CN119390440A_ABST
Patent Text Reader

Abstract

The invention relates to a bismuth scandate-lead titanate based piezoelectric ceramic material and a preparation method and application thereof, the chemical general formula of the bismuth scandate-lead titanate based piezoelectric ceramic material is (1-y) Bi (Sc (1-x) Mex) O3-yPbTiO3, Me is a late transition metal element, x is 0.03-0.3, and y is 0.63-0.64. Compared with the prior art, the piezoelectric anisotropy and the piezoelectric property of the piezoelectric ceramic are improved by doping the rear transition group metal element Me on the basis of the BiScO3-PbTiO3 binary system piezoelectric ceramic material, the piezoelectric constant d33 is greater than 500pC / N, and the piezoelectric anisotropy d33 / d31 is greater than 3.5.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of piezoelectric ceramic materials, and in particular to a bismuth scandate-lead titanate-based piezoelectric ceramic material and a preparation method and application thereof. Background Art

[0002] Piezoelectric materials are special functional materials that can realize the mutual conversion of electrical energy and mechanical energy. As a typical piezoelectric material, lead zirconate titanate PZT piezoelectric ceramics have the advantages of good temperature stability, strong anti-electromagnetic interference ability, and excellent mechanical and electrical properties. They have received extensive attention and research in the preparation and application of devices such as sensors, transducers, underwater sonar, medical ultrasound imaging, and piezoelectric motors. However, the electromechanical anisotropy k of PZT ceramics is t / k p Less than 1, piezoelectric anisotropy |d 33 / d 31 |It is only about 2.4. When the sensor device made of PZT ceramic is used in the field of ultrasonic non-destructive testing, the small anisotropy causes the parasitic mode to interfere greatly with the main vibration mode, thus affecting the accuracy and stability of the resonant frequency and reducing the resolution; in the field of underwater acoustics, the underwater acoustic transducer used for high-power transmission is composed of linearly arranged rectangular piezoelectric ceramic vibrators separated from each other. When the width-to-thickness ratio W / T of the PZT ceramic vibrator is ≥1, there is a strong coupling between the thickness mode and the lateral mode and other modes, which not only shortens the detection distance of the transducer but also reduces the resolution of the system.

[0003] Therefore, developing new materials with excellent piezoelectric properties and large piezoelectric anisotropy, reducing the interference of parasitic modes on the main vibration mode, and enhancing the signal-to-noise ratio and sensitivity of sonar detection systems have become hot topics in current research.

[0004] PbTiO 3 Compared with PZT ceramics, ceramics have high Curie temperature (490°C) and low dielectric constant (ε r = 200) and large piezoelectric anisotropy (|d 33 / d 31 |﹥8) and other advantages. After being made into a piezoelectric device, the transducer and the medium can be fully coupled without interference from parasitic modes, which increases the detection distance and improves the system resolution. 3 The ceramic has a large tetragonal distortion (c / a=1.063). The phase transition from cubic phase to tetragonal phase when passing through the Curie point will produce large stress, making the ceramic easy to pulverize and difficult to sinter. At the same time, the excessive coercive field makes PbTiO 3 Ceramics are difficult to fully polarize, and the piezoelectric constant d 33 Only 56pC / N.

[0005] Bismuth scandate-lead titanate (BiScO 3 -PbTiO 3 ) binary solid solution with its excellent piezoelectric properties (d 33 =450pC / N) has attracted widespread attention. In addition, compared with PZT ceramics, the piezoelectric anisotropy of BS-PT ceramics |d 33 / d 31 |>3, which significantly enhances its bandwidth, sensitivity and resolution in the field of transducers and sensors. Summary of the invention

[0006] The purpose of the present invention is to provide a bismuth scandate-lead titanate-based piezoelectric ceramic material and its preparation method and application based on bismuth scandate-lead titanate to further improve its anisotropy and piezoelectric properties.

[0007] The purpose of the present invention can be achieved by the following technical solutions:

[0008] One of the technical solutions of the present invention is to provide a bismuth scandate-lead titanate-based piezoelectric ceramic material, wherein the chemical formula of the bismuth scandate-lead titanate-based piezoelectric ceramic material is (1-y)Bi(Sc (1-x) Me x ) 3 -yPbTiO 3 , wherein Me is a post-transition metal element, x=0.03~0.3, y=0.63~0.64.

[0009] In some embodiments, the Me is selected from Al 3+ , Ga 3+ ,In 3+ , Tl 3+ ,Ge 4+ , Sb 5+ Any one of .

[0010] This technical solution is in BiScO 3 -PbTiO 3 The doped late transition metal element Me replaces the perovskite structure ABO based on the binary piezoelectric ceramic material 3 The cation at position B in the structure. According to the principle of charge balance, high-valent ions such as Ge 4+ , Sb 5+ The doping of Al2O3 will cause a certain number of cation vacancies to appear in the lattice to maintain electrical neutrality. The formation of cation vacancies is conducive to the flipping of ferroelectric domains and the movement of domain walls, which reduces the coercive field strength of the ceramic and increases the residual polarization strength, making the ceramic easy to polarize. 3+ , Ga 3+ ,In 3+ , Tl 3+The doping of the same can easily lead to lattice distortion due to the difference in ion radius, which can regulate the microstructure and polarization state of piezoelectric ceramics, thereby affecting its piezoelectric effect and further enhancing the piezoelectric performance.

[0011] A second technical solution of the present invention is to provide a method for preparing the bismuth scandate-lead titanate-based piezoelectric ceramic material as described in one of the above technical solutions, comprising the following steps:

[0012] S1, according to the chemical composition (1-y)Bi(Sc (1-x) Me x ) 3 -yPbTiO 3 The oxides of Bi, Sc, Pb, Ti and Me are weighed and mixed in a stoichiometric ratio, and then dried and calcined in stages;

[0013] S2, adding a binder to the mixed material treated in step S1, pressing and molding, and obtaining a ceramic blank after a binder removal treatment;

[0014] S3, sintering the ceramic green body obtained in step S2 to obtain a dense ceramic sheet, namely, a bismuth scandate-lead titanate-based piezoelectric ceramic material.

[0015] In some specific embodiments, in step S1, the raw materials are weighed and mixed by wet planetary ball milling.

[0016] In some specific embodiments, in step S1, the process conditions for ball milling are: adding 60%-75% of the total mass of ammonia water and / or ethanol to the mixed raw materials for wet ball milling, the ball mill speed is 150-300 rpm, and the ball milling time is 12-24 hours.

[0017] In some specific embodiments, in step S1, the drying temperature is 70-90°C.

[0018] In some specific embodiments, in step S1, the staged calcination includes a first stage calcination and a second stage calcination, wherein the first stage calcination process is: heating to 400-500°C at a heating rate of 4-5°C / min, and the calcination time is 1-4h; the second stage calcination process is: heating to 700-850°C at a heating rate of 4-5°C / min, and the calcination time is 4-10h.

[0019] In some specific embodiments, in step S1, ball milling, drying and calcination are repeated at least once after calcination.

[0020] In some specific embodiments, in step S2, the binder is polyvinyl alcohol (PVA), and the amount of the binder is 5-10% of the total mass of the mixed powder.

[0021] In some specific embodiments, in step S2, the process conditions of the debinding treatment are: the debinding temperature is 450-600° C., and the debinding time is 8-24 hours.

[0022] In some specific embodiments, in step S3, the sintering process conditions are: heating to 1020-1080° C. at a heating rate of 4-5° C. / min and then keeping the temperature for 2-6 hours.

[0023] The prepared bismuth scandate-lead titanate-based piezoelectric ceramic material was polarized for subsequent testing. The process conditions for polarization are: silver electrode is plated on the surface of dense ceramic sheet at 700℃, kept warm for 10-30min, and then polarized in 100-120℃ silicone oil, the polarization DC electric field strength is 3-6kV / mm, and the polarization time is 30-60min.

[0024] The third technical solution of the present invention is to provide an application of the bismuth scandate-lead titanate-based piezoelectric ceramic material as described in one of the above technical solutions, wherein the bismuth scandate-lead titanate-based piezoelectric ceramic material is used to prepare sensitive components.

[0025] Compared with the prior art, the present invention has the following beneficial effects:

[0026] (1) The present invention provides a bismuth scandate-lead titanate-based piezoelectric ceramic material. Bismuth scandate and lead titanate have similar structures, both of which are perovskite structures and can form a binary solid solution. By adjusting the phase boundary, the piezoelectric coefficient of the system is significantly improved. The incorporation of the post-transition metal element Me makes the grain size of the piezoelectric ceramic within the range of 2-4μm, which not only reduces the pinning effect of the grain boundary on the electric domain reversal, but also avoids the reduction of mechanical strength and fracture toughness caused by excessive grain size. At the same time, the changes in lattice distortion, electronic structure and covalent bond characteristics caused by the difference in ionic radius improve the piezoelectric anisotropy of the piezoelectric ceramic, and the maximum piezoelectric constant d 33 >500pC / N, piezoelectric anisotropy|d 33 / d 31 |>3.5. In summary, the bismuth scandate-lead titanate-based piezoelectric ceramic material provided by the present invention can meet the needs of ultrasonic non-destructive testing, high-frequency transducers, sensors and other sensitive components, and has great potential in the application of sensors, actuators, transducers, medical imaging, military and defense and other fields.

[0027] (2) The piezoelectric ceramic material provided by the present invention can be prepared by a traditional solid-phase reaction method, and the preparation process is stable, the operation is simple, the cost is low, and it is suitable for large-scale industrial production, and has practical application value and broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1This is the XRD diffraction pattern of the bismuth scandate-titanate-based piezoelectric ceramic material prepared in Example 1 of the present invention.

[0029] Figure 2 This is a SEM scanning electron microscope micrograph of the bismuth scandate-lead titanate-based piezoelectric ceramic material prepared in Example 1 of the present invention.

[0030] Figure 3 This is the XRD diffraction pattern of the bismuth scandate-titanate-based piezoelectric ceramic material prepared in Example 2 of the present invention.

[0031] Figure 4 This is a SEM scanning electron microscope micrograph of the bismuth scandate-lead titanate-based piezoelectric ceramic material prepared in Example 2 of the present invention.

[0032] Figure 5 This is the XRD diffraction pattern of the bismuth scandate-titanate-based piezoelectric ceramic material prepared in Example 3 of the present invention.

[0033] Figure 6 This is a SEM scanning electron microscope micrograph of the bismuth scandate-lead titanate-based piezoelectric ceramic material prepared in Example 3 of the present invention.

[0034] Figure 7 The BSMe-PT ceramics, BS-PT ceramics, PbTiO prepared in Example 1 of the present invention 3 Ceramic and PZT-4 ceramic 33 with |d 33 / d 31 |Compare. DETAILED DESCRIPTION

[0035] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. This embodiment is implemented based on the technical solution of the present invention, and provides a detailed implementation method and specific operation process, but the protection scope of the present invention is not limited to the following embodiments.

[0036] In the following examples and comparative examples, unless otherwise specified, raw materials or processing techniques are conventional commercially available raw materials or conventional processing techniques in the art.

[0037] Embodiment 1:

[0038] This embodiment provides a chemical composition of (1-y)Bi(Sc (1-x) Ga x ) 3 -yPbTiO 3 , bismuth scandate-lead titanate based piezoelectric ceramics with x=0.10 and y=0.635.

[0039] The preparation method of the piezoelectric ceramic material is as follows:

[0040] a) Use analytically pure Bi 2 O 3 Sc 2 O 3 、PbO、Ga 2 O 3 and TiO 2 The raw material powder is prepared according to the above stoichiometric ratio, the raw material is placed in a ball mill, anhydrous ethanol is used as the ball milling medium, and the amount used is 80wt% of the total mass of the raw material. After mixing and ball milling in a planetary ball mill at a speed of 250r / min for 12 hours, the material is placed in a 90°C oven for rapid drying;

[0041] b) After drying, the mixed powder is sieved, heated to 450°C at a heating rate of 5°C / min and calcined for two hours, and then heated to 750°C at the same rate and calcined for four hours to obtain BSMe-PT powder with fine particles synthesized by single calcination;

[0042] c) crushing and grinding the BSMe-PT powder obtained by the primary calcination, and putting it into a ball mill, adding anhydrous ethanol of the same mass ratio, and performing secondary ball milling for 6 hours, and drying the material in an oven at 90°C;

[0043] d) heating the powder after the secondary ball milling to 450° C. at a heating rate of 5° C. / min and calcining it for two hours, and then heating it to 750° C. at the same rate and calcining it for 4 hours to obtain a secondary calcined BSMe-PT powder with fine particles and no impurities;

[0044] e) crushing and grinding the BSMe-PT powder obtained by secondary calcination and putting it into a ball mill, adding anhydrous ethanol of the same mass ratio and ball milling for three times for 6 hours, and drying the material in an oven at 90° C. to obtain BSMe-PT ceramic powder;

[0045] f) adding 5 wt% PVA binder to the BSMe-PT ceramic powder after three ball milling, grinding and granulating, aging, sieving, and then pressing at a pressure of 120 MPa into small discs with a diameter of 12 mm and a thickness of 0.8 mm, then heating to 450° C. for 4 hours and then heating to 600° C. for 4 hours, and finally cooling with the furnace to remove organic matter in the ceramic discs;

[0046] g) placing the small disc after debinding into a crucible with powder padding, heating the mixture to 1040° C. at a heating rate of 5° C. / min in a high-temperature sintering furnace and keeping the temperature for 2 hours, and then cooling the mixture in the furnace to obtain a bismuth scandate-lead titanate-based piezoelectric ceramic sample;

[0047] h) The upper and lower surfaces of the sintered dense ceramic sample were polished and processed into the required size, and then used as electrodes after silver brushing and silver burning. The silver burning treatment conditions were 700°C and the heat preservation time was 30 minutes. Then it was placed in 120°C silicone oil and polarized for 30 minutes under an electric field of 3kV / mm for performance testing.

[0048] XRD diffraction pattern and SEM scanning electron microscope image Figure 1 , 2 As shown, its comprehensive performance is as follows: 33 =510pC / N,k p =0.61,ε r =1260, tanδ=4.1%, Tc=440℃, Q m =18,|d 33 / d 31 |=3.7, and the average grain size is 3.5μm.

[0049] Embodiment 2:

[0050] This embodiment provides a chemical composition of (1-y)Bi(Sc (1-x) Ga x ) 3 -yPbTiO 3 , bismuth scandate-lead titanate based piezoelectric ceramics with x=0.12 and y=0.635.

[0051] The preparation method of the piezoelectric ceramic material is as follows:

[0052] a) Use analytically pure Bi 2 O 3 Sc 2 O 3 、PbO、Ga 2 O 3 and TiO 2 The raw material powder is prepared according to the above stoichiometric ratio, the raw material is placed in a ball mill, anhydrous ethanol is used as the ball milling medium, and the amount used is 80wt% of the total mass of the raw material. After mixing and ball milling in a planetary ball mill at a speed of 250r / min for 12 hours, the material is placed in a 90°C oven for rapid drying;

[0053] b) After drying, the mixed powder is sieved, heated to 450°C at a heating rate of 5°C / min and calcined for two hours, and then heated to 750°C at the same rate and calcined for four hours to obtain BSMe-PT powder with fine particles synthesized by single calcination;

[0054] c) crushing and grinding the BSMe-PT powder obtained by the primary calcination, and putting it into a ball mill, adding anhydrous ethanol of the same mass ratio, and performing secondary ball milling for 6 hours, and drying the material in an oven at 90°C;

[0055] d) heating the powder after the secondary ball milling to 450° C. at a heating rate of 5° C. / min and calcining it for two hours, and then heating it to 750° C. at the same rate and calcining it for 4 hours to obtain a secondary calcined BSMe-PT powder with fine particles and no impurities;

[0056] e) crushing and grinding the BSMe-PT powder obtained by secondary calcination and putting it into a ball mill, adding anhydrous ethanol of the same mass ratio and ball milling for three times for 6 hours, and drying the material in an oven at 90° C. to obtain BSMe-PT ceramic powder;

[0057] f) adding 5 wt% PVA binder to the BSMe-PT ceramic powder after three ball milling, grinding and granulating, aging, sieving, and then pressing at a pressure of 120 MPa into small discs with a diameter of 12 mm and a thickness of 0.8 mm, then heating to 450° C. for 4 hours and then heating to 600° C. for 4 hours, and finally cooling with the furnace to remove organic matter in the ceramic discs;

[0058] g) placing the small disc after debinding into a crucible with powder padding, heating the mixture to 1040° C. at a heating rate of 5° C. / min in a high-temperature sintering furnace and keeping the temperature for 2 hours, and then cooling the mixture in the furnace to obtain a bismuth scandate-lead titanate-based piezoelectric ceramic sample;

[0059] h) The upper and lower surfaces of the sintered dense ceramic sample were polished and processed into the required size, and then used as electrodes after silver brushing and silver burning. The silver burning treatment conditions were 700°C and the heat preservation time was 30 minutes. Then it was placed in 120°C silicone oil and polarized for 30 minutes under an electric field of 3kV / mm for performance testing.

[0060] XRD diffraction pattern and SEM scanning electron microscope image Figure 3 , 4 As shown, its comprehensive performance is as follows: 33 =463pC / N,k p =0.57,ε r =1116, tanδ=5.0%, Tc=430℃, Q m =18,|d 33 / d 31 |=3.5, the average grain size is 2μm.

[0061] Embodiment 3:

[0062] This embodiment provides a chemical composition of (1-y)Bi(Sc (1-x) Ga x ) 3 -yPbTiO 3, bismuth scandate-lead titanate based piezoelectric ceramics with x=0.13, y=0.633.

[0063] The preparation method of the piezoelectric ceramic material is as follows:

[0064] a) Use analytically pure Bi 2 O 3 Sc 2 O 3 、PbO、Ga 2 O 3 and TiO 2 The raw material powder is prepared according to the above stoichiometric ratio, the raw material is placed in a ball mill, anhydrous ethanol is used as the ball milling medium, and the amount used is 80wt% of the total mass of the raw material. After mixing and ball milling in a planetary ball mill at a speed of 250r / min for 12 hours, the material is placed in a 90°C oven for rapid drying;

[0065] b) After drying, the mixed powder is sieved, heated to 450°C at a heating rate of 5°C / min and calcined for two hours, and then heated to 750°C at the same rate and calcined for four hours to obtain BSMe-PT powder with fine particles synthesized by single calcination;

[0066] c) The BS-PT powder obtained by the primary calcination was crushed and ground, and then put into a ball mill, and anhydrous ethanol of the same mass ratio was added, and a secondary ball milling was performed for 6 hours, and the material was discharged and dried in an oven at 90°C;

[0067] d) heating the powder after the secondary ball milling to 450° C. at a heating rate of 5° C. / min and calcining it for two hours, and then heating it to 750° C. at the same rate and calcining it for 4 hours to obtain a secondary calcined BSMe-PT powder with fine particles and no impurities;

[0068] e) crushing and grinding the BSMe-PT powder obtained by secondary calcination and putting it into a ball mill, adding anhydrous ethanol of the same mass ratio and ball milling for three times for 6 hours, and drying the material in an oven at 90° C. to obtain BSMe-PT ceramic powder;

[0069] f) adding 5 wt% PVA binder to the BSMe-PT ceramic powder after three ball milling, grinding and granulating, aging, sieving, and then pressing at a pressure of 120 MPa into small discs with a diameter of 12 mm and a thickness of 0.8 mm, then heating to 450° C. for 4 hours and then heating to 600° C. for 4 hours, and finally cooling with the furnace to remove organic matter in the ceramic discs;

[0070] g) placing the small disc after debinding into a crucible with powder padding, heating the mixture to 1040° C. at a heating rate of 5° C. / min in a high-temperature sintering furnace and keeping the temperature for 2 hours, and then cooling the mixture in the furnace to obtain a bismuth scandate-lead titanate-based piezoelectric ceramic sample;

[0071] h) The upper and lower surfaces of the sintered dense ceramic sample were polished and processed into the required size, and then used as electrodes after silver brushing and silver burning. The silver burning treatment conditions were 700°C and the heat preservation time was 30 minutes. Then it was placed in 120°C silicone oil and polarized for 30 minutes under an electric field of 3kV / mm for performance testing.

[0072] XRD diffraction pattern and SEM scanning electron microscope image Figure 5 , 6 As shown, its comprehensive performance is as follows: 33 =480pC / N,k p =0.55,ε r =1160, tanδ=4.5%, Tc=418℃, Q m =19,|d 33 / d 31 |=3.65.

[0073] Comparative Example 1:

[0074] Compared with Example 1, most of the aspects are the same, the only difference is that the doping of Me(Ga) is omitted.

[0075] Figure 7 The BSMe-PT ceramics prepared in Example 1, the BS-PT ceramics prepared in Comparative Example 1, and PbTiO 3 Ceramic and PZT-4 ceramic 33 with |d 33 / d 31 | By comparison, it can be seen that the piezoelectric constant and piezoelectric anisotropy of the BSMe-PT ceramics prepared by the present invention are effectively improved. 3 Ceramics and PZT-4 ceramics are commercial products purchased from Shandong Zibo Yuhai Electronic Ceramics Co., Ltd.

[0076] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.

Claims

1. A bismuth scandate-lead titanate-based piezoelectric ceramic material, characterized in that: The chemical formula of the bismuth scandate-lead titanate based piezoelectric ceramic material is (1-y)Bi(Sc (1-x) Me x )O3-yPbTiO3, wherein Me is a post-transition metal element, x=0.03~0.3, y=0.63~0.

64.

2. The bismuth scandate-lead titanate-based piezoelectric ceramic material according to claim 1, characterized in that: The Me is selected from Al 3 + , Ga 3+ ,In 3+ , Tl 3+ ,Ge 4+ , Sb 5+ Any one of .

3. A method for preparing the bismuth scandate-lead titanate-based piezoelectric ceramic material according to claim 1 or 2, characterized in that: The steps include: S1, according to the chemical composition (1-y)Bi(Sc (1-x) Me x )O3-yPbTiO3 stoichiometric ratio of raw materials Bi, Sc, Pb, Ti and Me oxides are weighed and mixed, and then dried and calcined in stages; S2, adding a binder to the mixed material treated in step S1, pressing and molding, and obtaining a ceramic blank after a binder removal treatment; S3, sintering the ceramic green body obtained in step S2 to obtain a dense ceramic sheet, namely, a bismuth scandate-lead titanate-based piezoelectric ceramic material.

4. The method for preparing the bismuth scandate-lead titanate-based piezoelectric ceramic material according to claim 3, characterized in that: In step S1, the raw materials are weighed and mixed by wet planetary ball milling; the process conditions of ball milling are: adding 60%-80% of the total mass of the mixed raw materials with ammonia water and / or ethanol for wet ball milling, the ball mill speed is 150-300 rpm, and the ball milling time is 12-24 hours.

5. The method for preparing the bismuth scandate-lead titanate-based piezoelectric ceramic material according to claim 3, characterized in that: In step S1, the staged calcination includes a first stage calcination and a second stage calcination, wherein the first stage calcination process is: heating to 400-500°C at a heating rate of 4-5°C / min, and the calcination time is 1-4h; the second stage calcination process is: heating to 700-850°C at a heating rate of 4-5°C / min, and the calcination time is 4-10h.

6. The method for preparing the bismuth scandate-lead titanate-based piezoelectric ceramic material according to claim 3, characterized in that: In step S1, after one stage calcination, ball milling, drying and stage calcination are repeated at least once.

7. The method for preparing the bismuth scandate-lead titanate-based piezoelectric ceramic material according to claim 3, characterized in that: In step S2, the binder is polyvinyl alcohol, and the amount of the binder used is 5-10% of the total mass of the mixed powder.

8. The method for preparing the bismuth scandate-lead titanate-based piezoelectric ceramic material according to claim 3, characterized in that: In step S2, the process conditions for the debinding treatment are: the debinding temperature is 450-600° C., and the debinding time is 8-24 hours.

9. The method for preparing the bismuth scandate-lead titanate based piezoelectric ceramic material according to claim 3, characterized in that: In step S3, the sintering process conditions are: heating to 1020-1080° C. at a heating rate of 4-5° C. / min and then keeping the temperature for 2-6 hours.

10. An application of the bismuth scandate-lead titanate-based piezoelectric ceramic material as claimed in claim 1 or 2, characterized in that: The bismuth scandate-lead titanate-based piezoelectric ceramic material is used to prepare sensitive components.

Citation Information

Patent Citations

  • Bismuth scandate-lead titanate-based high-temperature piezoelectric ceramic with low high-temperature loss and preparation method of bismuth scandate-lead titanate-based high-temperature piezoelectric ceramic

    CN114853466A

  • High-temperature stable piezoelectric ceramic material with high electro-mechanical transformation coefficient and preparation method of high-temperature stable piezoelectric ceramic material

    CN116553924A

  • High-temperature piezoelectric ultrasonic transducer, preparation method and application thereof

    CN117427865A

  • Oriented ceramic and manufacturing method therefor, and piezoelectric element

    JP2019108260A

  • Piezoelectric properties enhanced bismuth-perovskite composition and the enhancing method of the same

    KR1020100009000A

Cited By

  • High-temperature piezoelectric ceramic, preparation method thereof and high-temperature piezoelectric device

    CN121005567A

  • Bismuth scandate and lead titanate based high-temperature piezoelectric ceramic, driver and preparation method

    CN121248284A